Evaluation of Mineral Elements in Gentiana rigescens in China - Zhao, Yan-Li; Zhang, Ji; Yuan, Tian-Jun; Zhang, Jin-Yu; Shen, Tao; Wang, Yuan-Zhong; Jin, Hang (Asian Journal of Chemistry, 2014)
Gentiana rigescens is an important traditional Chinese herbal medicine. Mineral elements play an important role in the formation of active components in medicinal plants. This study aimed to determine nine mineral elements in G. rigescens collected from 41 different sites in Yunnan and Guizhou provinces of China by atomic absorption spectroscopy. The average concentrations of mineral elements were in the order of K > Ca > Mg > Fe > Na > Zn > Cu > Cr > Se. According to correlation analysis, Zn-Cu had the highest positive correlation (r = 0.834), while Fe-Mg were the strongest negatively correlated (r = -0.649) (p < 0.01). Three significant groups classified by principal component analysis contained more than 71.39 % of all the important influential sources. This study provides a comprehensive survey of the concentrations of 9 mineral elements in wild G. rigescens samples collected from different sites in Yunnan and Guizhou provinces of China. Magnesium, Fe, Zn and Cu, were viewed as the characteristic mineral elements of G. rigescens according to principal component analysis.